2001
DOI: 10.1054/bjoc.2001.1920
|View full text |Cite
|
Sign up to set email alerts
|

Betel nut and tobacco chewing; potential risk factors of cancer of oesophagus in Assam, India

Abstract: Summary Cancer of the oesophagus is the most commonly diagnosed cancer in males in Assam, in north-eastern India, and ranks second for females. The chewing of betel nut, with or without tobacco and prepared in various ways, is a common practice in the region and a case-control study has been designed to study the pattern of risk associated with different ways of preparing and chewing the nuts. 358 newly diagnosed male patients and 144 female have been interviewed together with 2 control subjects for each case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
79
0
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 11 publications
3
79
0
4
Order By: Relevance
“…13 The evidence for 2-way interaction of betel quid chewing with drinking and smoking was also examined in our study. Adjusted for the third habit and possible confounding variables, the joint risks for chewing and drinking as well as chewing and smoking were fitted well by a multiplicative model, a finding that is supported by earlier studies that have shown that a substantially higher cancer risk was marked among areca nut chewers who also drank alcohol 3,23,27 or smoked tobacco. 3,23 Considering chewing with or without tobacco as a category, one multicenter case-control study in Southern India found a multiplicative interaction effect between chewing and drinking as well as chewing and smoking.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…13 The evidence for 2-way interaction of betel quid chewing with drinking and smoking was also examined in our study. Adjusted for the third habit and possible confounding variables, the joint risks for chewing and drinking as well as chewing and smoking were fitted well by a multiplicative model, a finding that is supported by earlier studies that have shown that a substantially higher cancer risk was marked among areca nut chewers who also drank alcohol 3,23,27 or smoked tobacco. 3,23 Considering chewing with or without tobacco as a category, one multicenter case-control study in Southern India found a multiplicative interaction effect between chewing and drinking as well as chewing and smoking.…”
Section: Discussionsupporting
confidence: 77%
“…Adjusted for the third habit and possible confounding variables, the joint risks for chewing and drinking as well as chewing and smoking were fitted well by a multiplicative model, a finding that is supported by earlier studies that have shown that a substantially higher cancer risk was marked among areca nut chewers who also drank alcohol 3,23,27 or smoked tobacco. 3,23 Considering chewing with or without tobacco as a category, one multicenter case-control study in Southern India found a multiplicative interaction effect between chewing and drinking as well as chewing and smoking. 15 Although areca nut is chewed without tobacco in Taiwan, our results demonstrate that betel quid chewing modified the risk of drinking in determining the development of esophageal cancer based on an additive interaction model.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations